Supervised physical activity in patients with symptomatic peripheral arterial disease: protocol for a randomized clinical trial (ARTPERfit Study). Issue 4 (27th April 2022) - Alzamora, Maria Teresa; Forés, Rosa; Serra, Noemi; Martinez, Esau; Pera, Guillem; Seda, Gemma; Lopez Palencia, Joan; Gomis, Manuel; Heras Tébar, Antonio; Valverde, Marta; Garnacho, Manuel Vicente; Torán, Pere
Abstract : Introduction: Peripheral arterial disease (PAD) is a marker of cardiovascular morbidity, causing disability, loss of mobility and poor quality of life, manifesting clinically in the form of intermittent claudication (IC). Physical exercise increases the distance walked and improves quality of life. The aim of our study will be increased walking distance prolonging the time of onset of pain in patients with symptomatic PAD (IC). Methods and analysis: This study will be performed in Mataró Hospital's vascular surgery service and School of Health Sciences, TecnoCampus. This population comes from 15 primary healthcare centres ofNorth Barcelona, Spain (450 000 inhabitants). This study will be a four-group parallel, longitudinal, randomised controlled trial, blind to analysis. The main primary outcome of this study will be the improvement in pain-free walking distance. Others primary objectives are and improvement in functional status, quality of life and Ankle-Brachial Index (ABI). Secondary outcomes will be the analysis of cardiorespiratory fitness, evaluation of muscle fitness, determine the maintenance of primary objectives at 6 and 12 months. We will be included 124 patients (31 per group). The changes of the outcome (Barthel, SF-12, VascQOL-6, ABI) of the three intervention groups vs the control group at 3, 6 and 12 months will be compared, both continuously (linear regression) and categorically (logistic regression). A person who has not performed at least 75% of the training will be considered to have not completed the intervention. Ethics and dissemination: The study will be conducted according to the Declaration of Helsinki . It was approved by the Ethics Committee of the Research Institute Primary Health IDIAP Jordi Gol (20/035 P), Barcelona 6 October 2020. Informed consent will be obtained from all patients before the start of the study. We will disseminate results through academic papers and conference presentations. Trial registration number: NCT04578990 .